Polymyxin B: pharmacokinetics of single doses given intravenously and intramuscularly to turkeys, and minimal inhibitory concentrations for Escherichia coli and Pasteurella multocida - Freidlin, P J; Hoexter, S; Bock, R; Ziv, G; Samberg, Y; Risenberg, R; Inbar, A (Zentralblatt für Veterinärmedizin. Reihe B, 1992)
The 50% and 90% minimal inhibitory concentrations (MIC50 and MIC90) of polymyxin B for avian Escherichia coli and Pasteurella multocida isolates were determined by the agar plate dilution method. Polymyxin B at approximate MIC level in serum was bactericidal for E. coli in 2 to 4 hours. Aqueous polymyxin B sulfate was administered by a single bolus intravenous injection into turkeys at 10,000 IU/kg, and by a single bolus intramuscular injection at 5,000, 10,000 or 20,000 IU/kg. Effective serum drug concentrations after intramuscular injection (MIC50 levels or greater) were maintained for E. coli for 7.0 hr (10,000 IU/kg) and 11.5 hr (20,000 IU/kg), and for P. multocida for 3.0 hr (10,000 IU/kg) and 4.1 hr (20,000 IU/kg). Pharmacokinetic parameters were calculated by non-compartmental methods. Elimination time half-lives, mean residence time, clearance, and apparent volume of distribution at steady state (Vdss) were all much higher for i.m. injection of 20,000 IU/kg than for i.m. injection of 10,000 IU/kg. We postulate that there exists a minimal tissue-interaction threshold concentration (MTC) at which polymyxin B can enter previously unavailable compartments or bind to previously refractory tissue components. Bioavailability of polymyxin B injected i.m. was 0.904 for the 10,000 IU/kg dose and 0.675 for the 20,000 IU/kg dose. Dosage intervals necessary to produce minimal steady state concentrations (Cssmin) equal to the MIC were calculated. Certain aspects of the use of the parameter Vdss, and limitations on the use of dosage interval calculations for polymyxin B, are discussed. One week after i.m. injection of polymyxin B at 10,000 IU/kg, high tissue drug levels were present, especially in bound form in liver. Following single injections, no toxic effects on turkeys were observed.